2000
DOI: 10.1300/j115v19n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Providers' Information Seeking

Abstract: Recent research studies describe typical information-seeking behavior of doctors, nurses, and other health care providers. This review identifies and analyzes thirty-nine studies and nine reviews published since 1990. The researchers are from many disciplines and often work in multi-disciplinary teams. They have used both quantitative and qualitative methods to gather self-report and observational data. In spite of the increased availability of online bibliographic and full-text sources in this decade, health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 3 publications
2
27
0
Order By: Relevance
“…professionals 38,39 prefer information obtained through social interaction and that when these care providers are engaging in direct patient care, electronic and text-based resources are less often accessed when information is required to resolve clinical uncertainty. 40 The preference for information through social interaction as opposed to that obtained from the published literature, including research and clinical practice guidelines, should not automatically be viewed as a problem.…”
Section: Implementing the Recommendations Of Nutritional Guidelinesmentioning
confidence: 99%
“…professionals 38,39 prefer information obtained through social interaction and that when these care providers are engaging in direct patient care, electronic and text-based resources are less often accessed when information is required to resolve clinical uncertainty. 40 The preference for information through social interaction as opposed to that obtained from the published literature, including research and clinical practice guidelines, should not automatically be viewed as a problem.…”
Section: Implementing the Recommendations Of Nutritional Guidelinesmentioning
confidence: 99%
“…Vehicles used to gather information include paper, computers, electronic media, and personal correspondence via telephone, fax, computer (e-mail, chat), or face-to-face conversations. In 2000, McKnight and Peet's study of health care providers' information seeking [1] found that in spite of the onset of the availability of online resources, clinicians were still using older, more traditional ways of gathering information.…”
Section: Introductionmentioning
confidence: 99%
“…There are many practical and ethical reasons for conducting a thorough search of the literature before beginning any project or forming policy, but this is seldom done even by a well-intentioned searcher 22 – 24. One reason may be that searchers limit their queries to databases with which they are familiar 25. The procedures for conducting systematic reviews for Cochrane and Community Preventive Services include consulting multiple literature databases to find articles that meet the authors’ inclusion criteria 26 27 Table 1.…”
Section: Discussionmentioning
confidence: 99%